Internet Intervention System for Elderly Hypertensive Patients Based on Hospital Community Family Edge Network and Personal Medical Resources Optimization. - Fanghua, Gong; Sanhui, Tang (Journal of Medical Systems, 2020)
In view of the contradiction between the medical service demand of elderly patients with hypertension and the ability of hospital, community and family medical service security, based on the optimization of the hospital community family edge network and personal medical resources, this paper designs an Internet intervention system for elderly patients with hypertension. Firstly, based on studying the process and problems of the three-dimensional medical and health management service of hospitals, communities and families, the multi-dimensional medical and health management service edge network is formed with the government and medical structure as the core and the community and family as the edge. Then, since ensuring the distributed balance of the edge network, according to the condition of individual patients, classified guidance is given to guarantee that severe patients and other patients can get timely and effective treatment, while minimizing hospital, community and family medical resources and resource wastage. Secondly, an Internet intervention system for elderly patients with hypertension and marginal network is designed by integrating the context of Internet intervention, multi-dimensional factors and the connotation of different interventions. The experimental results show that the resource optimization algorithm and the Internet intervention system have good performance in the implementation efficiency of the Internet intervention system, the optimization performance of personal medical resources, the multi-level efficiency of hospitals, communities and families, and the experience quality of elderly patients with hypertension.